2019
DOI: 10.5614/ejgta.2019.7.1.12
|View full text |Cite
|
Sign up to set email alerts
|

On the super edge-magic deficiency of join product and chain graphs

Abstract: A graph G is called super edge-magic if there exists a bijective function

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Ngurah and Simanjuntak [21] studied the SEMD of join products of a path, a star, and a cycle, respectively, with isolated vertices. Generally, they showed that the join product of a SEM graph with isolated vertices has finite SEMD.…”
Section: The Semd Of Join Product Of Union Of a Star And A Path With mentioning
confidence: 99%
See 1 more Smart Citation
“…Ngurah and Simanjuntak [21] studied the SEMD of join products of a path, a star, and a cycle, respectively, with isolated vertices. Generally, they showed that the join product of a SEM graph with isolated vertices has finite SEMD.…”
Section: The Semd Of Join Product Of Union Of a Star And A Path With mentioning
confidence: 99%
“…Generally, they showed that the join product of a SEM graph with isolated vertices has finite SEMD. In [22] , the same authors investigated the SEMD of join product of a graph G which has certain properties with an isolated vertex. They gave a necessary condition for to have zero SEMD as the following lemma.…”
Section: The Semd Of Join Product Of Union Of a Star And A Path With mentioning
confidence: 99%
“…Since then, this theory has been used to describe many fundamental issues or phenomena in operations research, chemistry, computer science, and social science. Numerous groups of authors have introduced and studied various graph generation models from different perspectives [1][2][3][4][5]. Additionally, it has been used in communication roads of cities, city maps, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Sugeng and Silaban provide bedge consecutive edge magic total labeling for some classes of regular trees [12] and disconnected graphs [10]. For graphs that don't admit SEMTL, Ngurah and Simanjuntak [7,8] add isolated vertices such that the graph admits SEMTL. The number of isolated vertices added is called the super edge magic deficiency.…”
Section: Introductionmentioning
confidence: 99%